Analisis Sentimen pada Media Sosial dengan Teknik Kecerdasan Buatan Naïve Bayes: Kajian Literatur Review - Amirulah Kaharudin; Ari Agus Supriyadi; Muhlis; Haqun Baitika; Muhamad Derryanur (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This study discusses sentiment analysis on social media using Naïve Bayes artificial intelligence (AI) techniques. This study aims to provide a literature review on AI techniques used in sentiment analysis on social media. The data collection used in this study was to search for related articles from various literary sources using the Publish or Perish application (https://harzing.com/resources/publish-or-perish). There are 8 articles used in this study, which relate to sentiment analysis on social media with the use of artificial intelligence techniques. The method used in this research is a literature study by collecting information from relevant journal articles. Based on the results and discussion of this study, it can be concluded that the use of artificial intelligence techniques in sentiment analysis on social media can provide great benefits in processing large amounts of data in a relatively short time, as well as recognizing certain patterns in the data. However, the use of artificial intelligence techniques in sentiment analysis on social media also has challenges, such as issues of accuracy, privacy and ethics. The implications of sentiment analysis on social media with AI techniques is a rapidly growing field of research and has various benefits for various sectors. Therefore, further research and development of AI technology is expected to help improve the quality of human life.